Kedai Kopi Bersahaja's Digital Marketing Strategy in Increasing Customer Purchase Interest - Nabela, Oktavia T; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research Objective: Analyzing the implementation of Kedai Kopi Bersahaja's digital marketing strategy through social media in increasing customer buying interest. Design/Methods/Approach: Using a qualitative phenomenological approach, this study involved in-depth interviews with three informants who were selected based on the criteria of relevance, recommendation, rapport, readiness, and reassurance. Data analysis was conducted through a process of data collection, data reduction, data presentation, and data verification. Data validity was tested using time triangulation. Research Findings: The results show that Instagram is the main platform that supports Kedai Kopi Bersahaja's digital marketing strategy. Features such as feeds, stories, and reels have proven effective in facilitating promotion and direct interaction with customers. Meanwhile, TikTok also plays a role in reaching younger audiences with creative and entertainment content. The most popular type of content is videos with audio-visual elements, which not only attract attention but also provide more information to customers. Aesthetic and authentic visual content can create a stronger emotional connection with customers, increase engagement, and drive purchase decisions. Theoretical Contribution/Originality: This research makes a theoretical contribution by showing how social media, especially Instagram, can be used strategically in digital marketing to increase customer buying interest in the MSME sector, especially in the coffee shop industry. Practical/Policy Implications: The results of the study provide recommendations for MSME players to make more optimal use of social media features, improve consistency and variety of content, and use a more creative and interactive approach to reach a wider audience. Research Limitations: Research limitations include the limited number of informants and focus on certain social media platforms, so it is recommended for further research to cover other platforms and involve more informants.